2020
DOI: 10.32473/joci.v2i4.127489
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Note: A Sickness that Lingers

Abstract: Nearly a year into the COVID-19 pandemic and we continue to see government restrictions on the flow of civic information to the public. The question is, will these restrictions linger long after the pandemic is over?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…26 The results were consistent with Cuillier's study of MuckRock data and demographics, where he found that political culture of a state was the greatest predictor of compliance with freedom of information laws. 27 Post-hoc analysis of the data examining statutory provisions suggested that response times were faster in states with a requirement for the agency to respond in one to five days (with an average response time of 51 days), as compared to states with no deadline (average response time of 60 days) or states with a deadline between six and 30 days (average response time of 63 days), and the author urged further study to see if those mean differences would be significant in a larger sample. 28 Cuillier's study also found no direct relationship between agencies complying with open records laws and the strength of penalties or other enforcement remedies in those laws, but it did find a connection between the presence of attorney fee-shifting provisions in the statutes.…”
Section: Introductionmentioning
confidence: 99%
“…26 The results were consistent with Cuillier's study of MuckRock data and demographics, where he found that political culture of a state was the greatest predictor of compliance with freedom of information laws. 27 Post-hoc analysis of the data examining statutory provisions suggested that response times were faster in states with a requirement for the agency to respond in one to five days (with an average response time of 51 days), as compared to states with no deadline (average response time of 60 days) or states with a deadline between six and 30 days (average response time of 63 days), and the author urged further study to see if those mean differences would be significant in a larger sample. 28 Cuillier's study also found no direct relationship between agencies complying with open records laws and the strength of penalties or other enforcement remedies in those laws, but it did find a connection between the presence of attorney fee-shifting provisions in the statutes.…”
Section: Introductionmentioning
confidence: 99%